Transboundary Haze Pollution in Indonesia and Malaysia in the Perspective of Islamic Law and International Environmental Law - Thoat Hamim; Muhamad Muslih; Eki Furqon (UNIFIKASI : Jurnal Ilmu Hukum, 2023)
The background of the research is that cross-border haze pollution that hits Indonesia and Malaysia occurs almost every year and this problem has not been resolved from the past until now. Humans, as the caliphs of Allah SWT on earth, are still unable to maximize their duties in preserving nature, forests and the environment. The aim of the research is to find out the latest issues in the problem of cross-border haze pollution in Indonesia and Malaysia so that we can analyze solutions according to Islamic law and international environmental law. The research method used is normative juridical with a statutory approach, concept approach and case approach. Using qualitative descriptive methods. The results of the research are that the management of natural resources is not in accordance with the principles of international law, causing air pollution which has a negative impact on Indonesia and Malaysia. The research conclusion is that the biggest factor triggering the problem of smoke pollution is forest and land fires, which are mostly caused by human actions. Law enforcement in preventing and taking action against perpetrators is still not effective, especially since there is interference from powerful elements who take part. The research suggestion is that society in its role as caliph must be able to act wisely and judiciously in managing the natural wealth on this earth so that environmental sustainability will be maintained. The government must be proactive in collaborating with neighboring countries in overcoming the haze problem